INDUCTION OF SOMATIC EMBRYOGENESIS IN PHYTOLACCA TETRAMERA, MEDICINAL SPECIES OF ARGENTINA - Cordal, M. A. Basiglio; Adema, M.; Briones, V.; Villarreal, B.; Panarisi, M. H.; Abedini, W.; Sharry, S. (Emirates Journal of Food and Agriculture, 2014)
Phytolacca tetramera Hauman is an endemic species of the Province of Buenos Aires (Argentina), in danger of extinction. This species has active fungicides. The methanol extract of its berries possess antifungal activity against opportunistic fungal pathogens. The somatic embryogenesis technique relies on the formation of an embryo from a somatic cell, that is, without the need for the fusion of gametes (Tisserat et al, 1979), which facilitates mass production of in vitro plants. Obtaining somatic embryos gives us the ability to automate the production process in short periods of time and in a confined space. The technique is a necessary step to generate synthetic seeds. In order to adjust a protocol of somatic embryogenesis sections young leaves of Phytolacca tetramera obtained in vitro were placed in a Murashige and Skoog medium supplemented with 2, 4- dichlorophenoxyacetic acid at different concentrations. Somatic embryos were obtained directly from the cutting edge of the blade and embryogenic callus (indirect way) from the midrib.